Alternative Zakat Poverty Line in Kelantan, Malaysia - Ahmad Fahme Mohd Ali; Mohd Faisol Ibrahim; Muhammad Ridhwan Ab. Aziz (Universiti Sains Islam Malaysia, 2024)
This study attempts to analyse the zakat poverty line between regions (urban and rural) and differences between household head gender (male and female) among the poor and needy zakat recipients in Kelantan. The study is motivated by a few shortcomings of the current zakat distributions as well as an increasing amount of expenditure annually on the two categories of zakat recipients and yet the number of fuqara (poor) and masakin (needy) households is increasing. The current amount of zakat monthly distribution seems to raise some issues due to its weaknesses. This paper offers several alternative regional poverty line estimations with varying underlying assumptions. Using the Household Expenditure Survey 2014, poverty lines are estimated based on the consumption patterns of regional and gender household per capita expenditure. The regional poverty lines from these reference groups produced robust poverty measurement rankings across regions in the country. This study recommends the method of zakat distribution to be improved in order to strengthen the Muslims economy condition and then, it would facilitate poverty alleviation programs conducted by the zakat department.